Analisis Balanced Scorecard dalam Mengukur Kinerja Perusahaan: Studi pada PT. Anugerah Kartika Agro Cabang Gorontalo - Mahfiza Mahfiza (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
The purpose of this study was to determine the performance of PT. Anugerah Kartika Agro Gorontalo Branch with a balanced scorecard approach and analysis. There are four perspectives in measuring performance, namely financial perspective, customers, internal business processes, and growth and learning. The research method used is a quantitative method using ratio analysis. The sample was determined by using purposive sampling technique. The data sources used are financial data, financial reports. Based on the results of data analysis and discussion, it is concluded that the performance of PT. Anugerah Kartika Agro Gorontalo Branch using a balanced scorecard approach is good and describes the level of achievement above the target standard. With the performance from a financial perspective seen from the liquidity ratio, solvency and profitability are good. Customer perspective performance shows good performance. With customer retention, customer acquisition and customer satisfaction, respectively. The performance of the internal business process perspective is good seen from the innovation process and after sales service. And the learning and growth perspective performance is also well measured from employee retention and employee productivity. so the overall performance balance is good